2015
DOI: 10.1080/13676261.2015.1059925
|View full text |Cite
|
Sign up to set email alerts
|

Future-oriented or present-focused? The role of social support and identity styles on ‘futuring’ in Italian late adolescents and emerging adults

Abstract: 2015): Future-oriented or present-focused? The role of social support and identity styles on 'futuring' in Italian late adolescents and emerging adults, Journal of Youth Studies,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 81 publications
(102 reference statements)
2
22
1
2
Order By: Relevance
“…For example, Jachimowicz et al (2017) investigated the effect of community trust on reducing myopic decisions of low‐income individuals. Thus, the extent to which the economic factor influences behavioral decision or psychological outcome can be attenuated or amplified by the social factor, such as social support (Sica, Crocetti, Ragozini, Aleni Sestito, & Serafini, 2016) or social capital.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Jachimowicz et al (2017) investigated the effect of community trust on reducing myopic decisions of low‐income individuals. Thus, the extent to which the economic factor influences behavioral decision or psychological outcome can be attenuated or amplified by the social factor, such as social support (Sica, Crocetti, Ragozini, Aleni Sestito, & Serafini, 2016) or social capital.…”
Section: Discussionmentioning
confidence: 99%
“…In still other studies, no differences were found between males and females regarding levels of emotional engagement (e.g., Odağ, 2013). In terms of differences between males and females regarding social support from peers, women are more willing to ask for support from others and are also more pleased with the support they receive (e.g., Colarossi, 2001;Sica et al, 2016). The present study contributes to the literature of applied linguistics and EFL teaching and learning by investigating gender differences within the sample.…”
Section: Introductionmentioning
confidence: 88%
“…Research has identified differences between women and men in terms of identity styles, social support from peers, and emotional engagement. It has been reported that men score higher on diffuse-avoidance than their female counterparts (e.g., Berzonsky & Kinney, 2008;Sica et al, 2016;Soenens, Berzonsky, Vansteenkiste, Beyers, & Goossens, 2005). Additionally, in some investigations females have higher informational scores (e.g., Berzonsky, 2008), and in others, female students have higher normative scores (Soenens et al, 2005).…”
Section: Introductionmentioning
confidence: 98%
“…In this sense, the present study suggests vocational support schemes to enhance the future orientation of students and their skill in planning their future occupation in order to prevent identity irresolution and negative reconsideration, as well as to support flexibility and identity achievement. Indeed, the current study reveals the crucial role of "futuring" (the capacity to make future plans; Sica, Crocetti, Aleni Sestito, Ragozini, & Serafini, 2016) in self-definition. This evidence supports the contention of identity research that emphasizes the importance of the identity exploration and the orientation to the future to support vocational and occupational future choices (Oyserman, Bybee, Terry, & Hart-Johnson, 2004).…”
Section: Discussion and Clinical Implications: How This Study Providementioning
confidence: 99%